Ahmad Syafii Maarif dan Model Interpretasi al-Qur’an Kontekstual - Faruq, Umar; Naufal Cholily (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2022)
This paper aims to highlight the construction of Syafii Maarif’s Qur’anic thought and how he uses the Qur’an as an ideal foundation in the construction of religious and national thought. The paper argues that: first, the Qur’an in Syafii Maarif’s thought construction has become the epistemological foundation that underlies his entire philosophy of thought. This epistemological foundation brings Syafii to the paradigmatic framework, ethical framework and epistemological framework based on Qur’anic narratives. Second, although the Qur’an is used as an ideal foundation in the construction of his religious thought, Syafii’s interaction process with the Qur’an is not in a purely interpretative area. He did not get into the historical space of revelation, and only sufficed for ‘deductive’ meanings and then used it as the basis of his argument. It is in this area that Syafii then extracts Qur’anic values from verses that are clear (sarih) to be contextualized on religious and national issues he faces in the modern era.